Media Ekopedagik Dalam Pembelajaran (TPS) Think Pair Share Untuk Menunjang Hasil Belajar Peserta Didik - Made Adi Nugraha Tristaningrat; Komang Wahyu Wiguna; Komang Trisna Mahartini (STAHN Mpu Kuturan Singaraja, 2022)
In this paper, the author tries to relate the literature study related to the comparison of Eco pedagogic media with TPS (Think Pair Share) learning in supporting student learning outcomes. From several studies such as relevant studies coupled with supporting theories, it is stated that Eco pedagogic media and TPS (Think Pair Share) models will provide broad opportunities for students to be able to think and train their reasoning so that students can then work together in groups. and can explain and provide information to other students. Of course, the information obtained is sourced from Eco pedagogic media in the form of the surrounding environment. The hope is that this Eco pedagogic media in TPS (Think Pair Share) learning can be used as a reference for every educator in creating an optimal learning atmosphere.